Some Physicochemical Properties of Essential Oil Extracted from Cymbopogon Schoenanthus (L.) Spreng (Poaceae) by Steam Distillation - Yassin, Atif, A. A.; Babiker, S. A.; Abdel-Rahim, Awad, A. (Gezira Journal of Engineering and Applied Sciences, 2018)
ABSTRACT The study was directed to extract essential oil from Cymbopogon Schoenanthus (L.) Spreng ( Poaceae ) using steam distillation unit. The percentages of essential oil extracted from Cymbopogon Schoenanthus (L.) Spreng ( Poaceae ) by steam distillation and hydro distillation are 1.4% and 0.9% respectively. The composition of the essential oil is piperitone (14.89 %), terpinolene (11.14 %), elemol (10.40 %) and guaiol (9.28 %). Some physicochemical properties of essential oil were determined: refractive index is 1.4859; color is 2.5 (brown);  pH is 5.93; boiling point is 185 °C; flash point is 70°C; moisture content is 2.7%;  density and specific gravity are 0.92745 g/cm³ and 0.92922 respectively. The physicochemical properties of Cymbopogon Schoenanthus (L.) Spreng ( Poaceae ) essential oil are comparable with the physicochemical properties of Sweet Basil, Lantana Camara.L and Peppermint essential oils.